The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1258/ijsa.2010.010320
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma genitalium infection among HIV-positive women: prevalence, risk factors and association with vaginal shedding

Abstract: Summary: This study examined the prevalence and factors associated with Mycoplasma genitalium (MG) infection among HIV-positive women and the association between MG and vaginal HIV-1 RNA shedding. HIV-positive women attending an outpatient clinic in New Orleans, Louisiana, USA, from 2002 to 2005 were examined for a battery of sexually transmitted infections (STIs) and underwent a behavioural survey. A selected subset had a measurement of vaginal shedding analysed. Of the 324 HIV-positive women, 32 (9.9%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
3
22
2
Order By: Relevance
“…2,19 The education level of subjects with positive M. genitalium infection was similar between high school and academic or university graduates. In contrast to this study, Gatski et al 10 found that most of the subjects with positive PCR result for M. genitalium were less educated or equivalent to high school graduates (72%). Pe'pin et al 20 discovered a significant association between M. genitalium infection in Female Sex Worker (FSWs) in West Africa with the level of education from no formal education to elementary school.…”
Section: Mycoplasma Genitalium Infection Prevalence In Patients With contrasting
confidence: 99%
See 4 more Smart Citations
“…2,19 The education level of subjects with positive M. genitalium infection was similar between high school and academic or university graduates. In contrast to this study, Gatski et al 10 found that most of the subjects with positive PCR result for M. genitalium were less educated or equivalent to high school graduates (72%). Pe'pin et al 20 discovered a significant association between M. genitalium infection in Female Sex Worker (FSWs) in West Africa with the level of education from no formal education to elementary school.…”
Section: Mycoplasma Genitalium Infection Prevalence In Patients With contrasting
confidence: 99%
“…It was found by da Costa et al 13 that the average age of subjects with positive M. genitalium in HIV positive males was 43 years old. Gatski et al 10 revealed that the average age of the HIV positive females subjects who were positive for M. genitalium was less than 35 years old, which were the sexually active population. Another study conducted by Anagrius et al 16 The education level of subjects with positive M. genitalium infection was similar between high school and academic or university graduates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations